The spirituality of anatheism - Jasiński, Karol (Bogoslovni vestnik, 2025)
The purpose of the paper is to critically present the essential elements of the concept of anatheism and to show it as a form of spirituality. Its essential expression is human openness and response to the various ways of the divine presence and call. It consists of three parts. The first presents the main ideas of anatheism (return of God as “Other” in a new form after the disappearance of the previous one; type of experience rather than a theory; need to deconstruct the scholastic concept of God), the second shows it as a certain type of spirituality (a way of life in the form of responding to the calls of the imagined divinity), while the third indicates the main areas of experience of the divine call (things, events and persons).
Keywords: anateizem; anatheism; dogodkov; duhovnost; events; human encounters; spirituality; srečevanja ljudi; the sacramentality of things; zakramentalnost stvari